Oyster mushroom agrotourism development design in Kekeri, West Lombok - Ida Ayu Widhiantari; Joko Sumarsono; Amrullah; Syahroni Hidayat; Astri Iga Siska (Yayasan Siti Widhatul Faeha, 2025)
The development of oyster mushroom agrotourism in Kekeri, West Lombok, offers a strategic solution to improve the sustainability of the rural economy. This study aims to formulate an integrated and applicable agrotourism development Design and determine priority strategies. The research method combines qualitative methods (surveys, observations, interviews, FGD) and uses the Analytical Hierarchy Process (AHP) to analyze stakeholder data. The results of the AHP analysis indicate that diversification of processed products is the top-priority strategy (weighted at 0.570), followed by infrastructure strengthening (0.198), digital marketing & collaboration (0.126), and educational tour packages (0.107). To address the technical challenges posed by temperature and humidity fluctuations, integrating IoT (Internet of Things) technology into the oyster mushroom cultivation system is recommended. In conclusion, the development of oyster mushroom agrotourism in Kekeri is highly feasible and supported by strong local potential. The implementation of priority strategies, supported by innovative technology, is expected to add value, increase farmers’ income, and enable sustainable agrotourism.